2016
DOI: 10.2147/ott.s124311
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of survival rates between 3D conformal radiotherapy and intensity-modulated radiotherapy in patients with stage Ⅲ non–small cell lung cancer

Abstract: PurposeRandomized trials showing a clear survival benefit of intensity-modulated radiotherapy (IMRT) over 3-dimensional conformal radiotherapy (3D-CRT) in the treatment of lung cancer are lacking. This study compared the survival rates of patients with stage III non-small cell lung cancer who were treated with either 3D-CRT or IMRT and analyzed the prognostic factors for survival.MethodsFrom January 2008 to July 2015, 19 patients were treated with IMRT and 30 were treated with 3D-CRT in our institution. The ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…4,5 The 5-year survival of stage IV NSCLC patients is as low as 1%. 6,7 Therefore, it is of great clinical significance to investigate the molecular mechanism of occurrence and development of NSCLC to improve the early diagnosis rate, predicting the prognosis, and improving the survival rate of patients.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…4,5 The 5-year survival of stage IV NSCLC patients is as low as 1%. 6,7 Therefore, it is of great clinical significance to investigate the molecular mechanism of occurrence and development of NSCLC to improve the early diagnosis rate, predicting the prognosis, and improving the survival rate of patients.…”
Section: Introductionmentioning
confidence: 99%
“…Although the current therapeutical treatment for NSLCC including surgery, molecular‐targeted therapy, and chemotherapy has been progressed tremendously in the last several decades, the prognosis is still poor with high metastasis of the NSLCC . The 5‐year survival of stage IV NSCLC patients is as low as 1% . Therefore, it is of great clinical significance to investigate the molecular mechanism of occurrence and development of NSCLC to improve the early diagnosis rate, predicting the prognosis, and improving the survival rate of patients.…”
Section: Introductionmentioning
confidence: 99%
“…The IMRT technique has been recently used in DRT for NSCLC, but it remains unclear that this ILAS is useful for predicting steroid-RP in DRT with IMRT. The difference of radiation dose distribution 28 and clinical outcomes 29 , 30 between 3DCRT and IMRT has also been reported. However, in this study, to homogenize the patient background, patients treated with the IMRT technique were eliminated.…”
Section: Discussionmentioning
confidence: 93%
“…Comparison of 3D-CRT versus VMAT plans in the 9 patients treated by 3D-CRT showed a statistically significant difference only in terms of increased mean heart doses by 3D-CRT and increased V5 for bilateral lungs by VMAT. Though rates of radiation pneumonitis and radiation esophagitis have been proven to be lower in multiple studies with VMAT, 3D-CRT is the best available option in most LMIC (Low and Middle Income Countries) [7] , [8] , [26] , [27] , [28] .…”
Section: Discussionmentioning
confidence: 99%
“…18 F-fluorodeoxyglucose positron emission tomography-computed tomography (FDG PET-CT) based treatment planning helps in this regard by both better tumour and nodal delineation, thus potentially sparing normal tissue. Multiple studies have shown dosimetric benefits of intensity modulated radiation therapy (IMRT) over 3-dimensional conformal radiotherapy (3D-CRT) but no overall survival benefit has been demonstrated [5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%